2007
DOI: 10.1038/sj.eye.6703042
|View full text |Cite
|
Sign up to set email alerts
|

Amfenac increases the radiosensitivity of uveal melanoma cell lines

Abstract: Purpose To evaluate the proliferation rates of five human uveal melanoma (UM) cell lines after treatment with amfenac, a cyclooxygenase (COX)-2 inhibitor, and subsequent radiation exposure. Methods Five human UM cell lines (92.1, SP6.5, MKT-BR, OCM-1, and UW-1) and one human fibroblast cell line (BJ) were incubated with amfenac. Treated and non-treated cell lines were then exposed to various doses of c radiation: 0, 2, 4, 6, and 8 Gy. Sulphorhodamine-B assay was used to assess proliferation rates 48 h post-rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…However, some patients have to undergo subsequent enucleation because of radiotherapy-related complications. This situation has raised concerns on how to optimize the effectiveness of radiation treatment [6,7]. Therefore, knowledge of the factors that cause radioresistance is essential to optimize therapeutic strategies and prevent side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some patients have to undergo subsequent enucleation because of radiotherapy-related complications. This situation has raised concerns on how to optimize the effectiveness of radiation treatment [6,7]. Therefore, knowledge of the factors that cause radioresistance is essential to optimize therapeutic strategies and prevent side effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, after large-dose fraction irradiation treatment, up to 20% of patients undergo subsequent enucleation because of radiotherapy-related complications. This situation has raised concerns on how to optimize the effectiveness of radiation treatment [6,7]. Recent investigations of microRNAs (miRNAs), however, are changing our understanding of the tumor biology of UM and are helping us to identify novel targets for radiotherapy [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Barak et al102 demonstrated that serum VEGF increased significantly after metastatic development in UM patients and that it could serve as a biomarker for metastatic UM. Preclinical studies demonstrated that bevacizumab, a monoclonal anti-VEGF antibody, suppressed in vitro growth and in vivo hepatic micrometastasis of ocular melanoma cells 63. However, some in vitro studies have found paradoxical results, with an increase in tumor growth after bevacizumab treatment.…”
Section: Systemic Therapiesmentioning
confidence: 99%
“…More recently, radiotherapy has become the primary therapy for UM patients who are not candidates for surgery, and more and more UM patients are being treated by radiation with radioactive plaques, charged particles, and photons (Gragoudas and Marie Lane, 2005; Mueller et al., 2000; Singh and Kivela, 2005). However, human UM cell lines display a wide range of radiosensitivity and some are relatively radioresistant (Fernandes et al., 2008; Logani et al., 1995a; Soulieres et al., 1995; Van Den Aardweg et al., 2002). This raises concerns about the effectiveness of this form of treatment.…”
Section: Introductionmentioning
confidence: 99%